Relationship between the cytokine profile of supernatants of invasive breast carcinoma and its molecular and histopathological characteristics - A. I. Autenshlyus; S. A. Arkhipov; E. S. Mikhaylova; V. V. Arkhipova; N. A. Varaksin (Сибирский онкологический журнал, 2024)
The aim of the study was to analyze the correlation between the cytokine profile of supernatants of invasive breast carcinoma of a nonspecific type (IBC-NST) samples, histopathological and molecular genetic parameters of IBC-NST, expression of the CD34 as a marker of angiogenesis and metastasis to regional lymph nodes (RLN).Material and Methods. The production of 14 cytokines in IBC-NST biopsy samples from 28 patients aged 37–60 years was studied. The concentration of cytokines in the supernatants of biopsies (CCSB) was determined (in pg/ml) using enzyme immunoassay (ELISA). The expression of CD34 and markers of IBC-NST molecular subtypes (HER2/neu, ER, PR, Ki67) in IBC-NST biopsy samples was evaluated by immunohistochemical method. The relative content of tumor cells of different differentiation grade in the IBC- NST samples was evaluated by histopathological analysis.Results. The assessment of CCSB showed statistically significant differences in IFN-γ, G-CSF, IL-2, IL-10 and MCP-1 between patients of group I (with metastases in RLNs) and group II (without metastases in RLNs). In group I, the correlations between histopathological parameters (Her2/neu, CD34 and Ki67 expressions, % of mitoses and poorly-differentiated cancer cells) and CCSB (MCP-1, IL-18) were revealed. In group II, the correlations between CCSB (IL-2, VEGF-A, G-CSF, IL-1Ra) and histopathological parameters, such as expression of Her2/neu, CD34, PR, % of mitoses and well-differentiated cancer cells, were revealed. The ROC analysis showed that the presence or absence of metastases in RLNs can be predicted on the basis of CD34 expression levels and concentrations of IL-10, G-CSF, and MCP-1 in supernatants of IBC-NST biopsy samples. The quality of the model for stratifying patients into groups with and without RLN metastases, based on the assessment of the concentration of MCP-1 in the supernatants of IBC-NST biopsies, reached maximum values (AUC=1.000) with relatively high CD34 expression.Conclusion. The analysis of the data obtained showed that the assessment of CD34 expression and production of cytokines in IBC-NST biopsies is important for predicting the presence or absence of metastases in RLNs.